Maintenance system analysis of vehicles and air-conditioners at Universiti Malaysia Pahang - Rafidah, Rahim (2008)
This project deals with the maintenance system at JPPH for the analysis of the vehicles and air-conditioners maintenance system in Universiti Malaysia Pahang (UMP). The objective of this project is to ensure that vehicles and air-conditioners maintenance exercises are recorded in a systematic way and to ensure that vehicles and air-conditioners maintenance cost is in control. The scopes of this project are review breakdown history of vehicles and air-conditioners, review the maintenance cost of the vehicles and air-conditioners, and propose improvement of maintenance management. The improper trend is observed in 6-Month Periodic RM/km Ratio for Bas Mini and Van Mercedes. The analysis shows that the cost of breakdown for both vehicles is not justified. Wira has the highest Average RM/km ratio among the cars. Therefore, the usage of Wira should be minimized in order to reduce its maintenance cost or another alternative is scrapped this vehicle. Investigation for the root cause of breakdown whether due to low quality product or human mishandling is never been carried out. Current maintenance exercises of air-conditioner shows that the cost for the maintenance operation are not recorded, location for the air-conditioners units are not specific and many tag number are not in place. The breakdown history of air-conditioner has never been prepared and the Work Order is not utilized properly. Repeated type of breakdown also occurred in the sample analysis of Fakulti Kejuruteraan Mekanikal (FKM).